In the Era of Computers, Internet and Multimedia, are we still Teaching Composers to become Chapel-Masters? - de Souza, Rodolfo Coelho (Revista Vórtex, 2020)
The ongoing paradigm shift from traditional methods of teaching music composition towards new approaches based on computer technology for sound production is the main focus of the article. The paper reviews the evolution of teaching methods throughout the Classical, Romantic and Modern periods, demonstrating how certain standard practices from former ages, based on the professional profile of the Chapel-Master, become theoretical golden principles for subsequent periods. After the French Revolution the traditional method of individual practical exchange between master and disciple was upgraded at the Conservatory. Classes for groups of students required a new approach based on theory abstraction. Although none of these teaching methods have been abandoned up today, a new paradigm appears when the tools of computer technology became widespread. An unpredictable equilibrium between the traditional methods and the new techniques of computer-assisted or computer-generated music composition tends to emerge.